Genetic regulation of heart valve development: Clinical implications - Marc-Phillip Hitz; Thomas Brand; Gregor Andelfinger (Global Cardiology Science & Practice, 2011)
Cardiac malformations, most commonly valve defects, are some of the predominant causes of cardiovascular morbidity and mortality worldwide. Up to a third of all patients with complex congenital heart defects and numerous syndromic conditions, as well as a significant amount of the general population, exhibit valve defects. These observations have not only major implications in infancy; they also have a major impact on the adult population and the growing number of adults with congenital malformations. Over recent years, a large number of Mendelian inheritance patterns and syndromic causes have been identified, shedding light on the importance of genes encoding components of the extracelluar matrix in valve disease. Nevertheless, we still know little about the genetic origin of sporadic and more complex family traits. It is unclear to what extent genetic variations play a role in disease pathogenesis and influences phenotypes rooted in early development. Such knowledge would be greatly beneficial for counseling and treatment of patients. Therefore, this review summarizes the findings in human non-syndromic and syndromic valve disease with a special focus on extracellular matrix proteins, and discusses them in the context of vertebrate valve development.